Prevalence of gastrointestinal helminthiasis in guinea pigs (Cavia porcellus) of small-scale farming in Junín, Peru - Ríos Z., Walter (2020)
The aim of this study was to estimate the prevalence of gastrointestinal helminthiasis in guinea pigs of small-scale farming of Matahuasi district, Concepción province, Junín-Peru, as well as to determine the genera and species of gastrointestinal helminths, load and type of parasitism (monoparasitism, biparasitism or polyparasitism), degree of concordance between the differential count of parasites to post mortem examination vs coprological techniques and the sensitivity/specificity of coprological techniques in the diagnosis of gastrointestinal helminthiasis in guinea pigs. Gastrointestinal tracts of guinea pigs (n=262) were acquired from slaughtering centres between January and March 2017. The stomach, small intestine and large intestine segments were evaluated to determine the parasitic load and faecal samples were collected from the rectum. Sample analysis was performed by differential count of parasites on post-mortem examination and complementary coprological techniques (Flotation and modified Dennis). The prevalence of gastrointestinal helminths was 82.8 ± 4.6%. Paraspidodera uncinata, Capillaria spp, Trichostrongylus axei and Trichuris spp were identified with frequencies of 74, 34, 6.1 and 3.4% respectively. The average number of helminths per animal was 24.7, where P. uncinata, Capillaria spp, Trichostrongylus axei and Trichuris spp showed averages of 23.5, 8.7, 1.2 and 1.2, respectively The monoparasitism was 50.4% and the biparasitism was 30.2% The degree of concordance between the coprological techniques presented values of Kappa (K) equal to 0.19 and 0.13 indicating poor concordance. The Flotation technique and the modified Dennis technique presented a sensitivity of 39.6 and 29.5% and a specificity of 89.9 and 93.3%, respectively.